Miniature dual‐band bandpass filter using modified quarter‐wavelength SIRs with controllable passbands. Issue 1 (1st January 2019) - Ren, Baoping; Ma, Zhewang; Liu, Haiwen; Guan, Xuehui; Wen, Pin; Wang, Xiaolong; Masataka, Ohira
Abstract : A modified quarter‐wavelength ( λ /4) stepped‐impedance resonator (SIR) is proposed to design a miniature dual‐band bandpass filter (BPF). The proposed λ /4 SIR has two individually controllable resonances for constructing dual passbands. Moreover, two independent geometrical parameters are adopted to realise individual adjustment of the coupling strengths between two adjacent λ /4 SIRs at the dual passbands. As a result, both the centre frequencies and bandwidths of the two passbands of the filter can be individually designed. Furthermore, multiple transmission zeros are created by the introduced source‐load coupling, which improves highly the selectivity of both passbands. The dual‐band BPF is designed at 2.35 and 5.8 GHz, and its simulated and measured responses are presented and show good agreement.